Rough trade - Carrasco, Katrina, 1983- (MCD/Farrar, Straus and Giroux, 2024)
"In this propulsive follow-up to The Best Bad Things, Alma Rosales (and her alter ego, Jack Camp) is back as a stevedore and part-time opium smuggler"--